Impatiens kingdon-wardii (Balsaminaceae), a new species from Mt. Victoria (Natma Taung), Myanmar - Tanaka, Nobuyuki; Sugawara, Takashi; Aung, Mu Mu; Murata, Jin (Phytotaxa, 2015)
A new species, Impatiens kingdon-wardii Nob. Tanaka & T. Sugaw. (Balsaminaceae), is described and illustrated from Mt. Victoria (Natma Taung), northwestern Myanmar. This species is distinguished from any other species by the pink orbicular, densely pubescent lateral sepals, appearance of which is like two ears of the mouse, and upper lobes of lateral united petals with hairy club-shaped protuberance.